Health Education Approach In Congenital Hypothyroidism Screening: Sytematic Review - Ropitasari Ropitasari; Fanny Kartika Fajriyani; Nahdiyah Karimah; Fatiya 'Izzatuna Tsiqqoh (Journal of Health Promotion and Behavior, 2026)
Background: Congenital hypothyroidism (CH) is a preventable cause of intellectual disability in newborns if detected early through neonatal screening. Maternal knowledge and health promotion interventions are critical to ensure timely screening and treatment. This study systematically reviews evidence on maternal education, knowledge, attitude, and promotional strategies for CH screening. Subjects and Method: This study uses a systematic review conducted by searching for articles from several databases, namely ScienceDirect, MDPI, PubMed, Springer Nature Link, and Taylor & Francis Group and Google Scholar with a search range from 2019-2025. The keywords used to search for articles were "Education" OR "promotion" AND "congenital hypothyroidism" OR "neonatal hypothyroidism" OR "Congenital Thyroid disorder" OR "Primary congenital hypothyroidism" OR "Neonatal Thyroid" AND "newborn screening" OR "early screening"”. The articles included in this study are full-text research articles focusing on education about congenital hypothyroidism screening, utilizing quantitative methods. Articles were collected using the PRISMA flow chart. Results: There are 9 articles included in this review. Educational interventions and community service programs, significantly improved maternal knowledge and attitude toward CH screening. Higher maternal education was associated with better neonatal thyroid outcomes, including lower TSH levels and reduced incidence of screen-positive CH. Key barriers identified include limited maternal awareness, parental refusal, early postnatal discharge, and insufficient formal training for healthcare providers. Effective promotion strategies involved integrating CH education into antenatal care, leveraging social media, providing continuous training for health cadres, and conducting community-based awareness programs. Conclusion: Maternal education and structured promotion significantly enhance awareness and uptake of CH screening. However, challenges in healthcare infrastructure, parental compliance, and professional training persist.